Potencialidade da recirculação do lodo de decantadores de alta taxa em ETAs convencionais - Dias, Wércio de Freitas (2018)
The physico-chemical treatment of water in conventional ETAs generates waste, called ETA sludge, whose destination is a challenge under the economic, technical and environmental aspects. The disposal of this residue by Brazilian ETAs has been the water bodies, therefore, from the point of view of the minimization of environmental impacts and water economy, the work evaluates the possibility of reuse of the sludge from a high rate decanter (DATx), through the recirculation procedure. The research was developed with data from ETA Renato de Freitas, Uberlândia - MG, which presents a conventional station configuration the characterization of the filter wash water (ALF) was used as the guiding parameter for the DATx sludge discharges, since recirculation of the ALF is a practice adopted in ETAs. For this, the turbidity of the DATx sludge during the opening of the discharge valve was evaluated for the operating times of 6, 12 and 24 h. Once the DATx operating time was reached, a pretreatment was proposed for sedimentation tests, followed by the crude and clarified sludge recirculation tests, at 2 and 4% rates, in Jar Test jars. The DATx equation showed that after a 6 hour operation the sludge presented turbidity (39UNT) approximately to the value found in ALF (45 UNT) and absence of protozoa, Giardia spp. and Cryptosporidium spp. At the rate of 2%, recirculation with crude or clarified sludge yielded decanted water with remaining turbidity values below 2.8 NTU. Meanwhile, the 4% rate, the non-clarification of the sludge, led to the highest remaining turbidity value (9 UNT). The results showed that it is possible to obtain a reduction in the coagulant dosage of 4 to 13%, maintaining the quality of the water decanted